"INELI Balkans" by Lida Mantzourani | Future Library Unconference 2015 (Future Library, 2016)
: Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία Βουλγαρία, Βουλγαρία